Synthesis and Pro Coagulant Properties of New Amide Derivatives of Pyrimidin 8 ON 2 1 F Theophylline-9-Alkylcarboxylic Acids - Omeran Fhid, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Synthesis and Pro Coagulant Properties of New Amide Derivatives of Pyrimidin 8 ON 2 1 F Theophylline-9-Alkylcarboxylic Acids